Kalibrasi Metode Clark Dan Snyder Durasi 3 Jam Dan 6 Jam DAS Siak Bagian Hulu Dengan HEC-HMS - Rohman Rosyid; Yohanna Lilis Handayani; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Upper Siak watersheds have increased discharge due to land use change. This study aims to determine the method of transforming the Upper Siak watershed. Various hydrological modeling to calculate flood discharge has been developed, one of which used in this research is HEC-HMS (Hydrologic Engineering Center-Hydrologic Modeling System). The transform method used is the Clark method and the Snyder method for modeling the HEC-HMS output flood discharge. Input calibration is daily rainfall data, hourly discharge, and 2012 land use map. Based on the calibration results showed that the method of flood discharge Clark duration of 3 hours and 6 hours have Percent value error in peak flow of 0.00 and 0.02. Snyder method of 3 and 6 hours duration have error value in peak flow of 0.01 and 0.01.Keywords: land use change, calibration, flood discharge, HEC-HMS